Testing for causality in mean and variance between the stock market and the foreign exchange market: an application to the major central and eastern european countries - Koseoglu, Sinem Derindere
Skúmanie existencie kauzálneho vzťahu medzi akciovým trhom a devízovým trhom v Českej republike, Maďarsku, Poľsku a Turecku.